Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5507/ag.2015.020
|View full text |Cite
|
Sign up to set email alerts
|

Winter course experience: Towards a wider understanding of a dramaturgy approach

Abstract: for Experiential Education (AEE) or from the meaning used in wider international contexts. Nevertheless, the term is a literal translation of the Czech term zážitková pedagogika, the concept of which implies that outdoors is not the only viable environment and that adventure education is not the only means of personal development. Czech experiential education is unique with its use of dramaturgy (described later) and its purposeful use of games (R. Hanuš & Chytilová, 2009). Every course typically has its uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The teacher in role brings the "students into active participation in the event". Gintel's understanding of dramaturgy as cited from [5] Martin in [5] emphasizes the concept of the dramaturgy wave, used to balance the physical, creative, social, and reflective aspects of the course. In this study, the experiment class with dramaturgical teaching has been shown to achieve superior results in English test score in comparison with the control class.…”
Section: Resultsmentioning
confidence: 99%
“…The teacher in role brings the "students into active participation in the event". Gintel's understanding of dramaturgy as cited from [5] Martin in [5] emphasizes the concept of the dramaturgy wave, used to balance the physical, creative, social, and reflective aspects of the course. In this study, the experiment class with dramaturgical teaching has been shown to achieve superior results in English test score in comparison with the control class.…”
Section: Resultsmentioning
confidence: 99%